Compressive Characteristics and Fracture Simulation of Cerasus Humilis Fruit - Cheng Hao; Dongjin Yang; Liyang Zhao; Jianguo Yang; Tao Wang; Junlin He (Agriculture)
During the harvesting process of Cerasus humilis, the fruits are susceptible to compression and impacts from the combing teeth, leading to internal damage to the pulp and rupture of the peel. This compromises the quality of the harvested fruits and subsequent processing, resulting in significant economic losses. To investigate the mechanical behavior of Cerasus humilis fruit, this study measured the geometric parameters as well as the mechanical properties (failure load, elastic modulus, compressive strength, and fracture energy) of the peel, pulp, and core in both the axial and radial directions. A geometric model of Cerasus humilis fruit was constructed using three-dimensional reverse engineering technology. The rupture process of the fruit under compressive loading was simulated and analyzed using Abaqus software (Version 2023). The damage mechanisms were investigated, and the accuracy and reliability of the finite element model were validated through compression experiments. The experimental results indicated that the mechanical properties of the peel of Cerasus humilis fruit exhibited no significant differences between the axial and radial directions, allowing it to be regarded as an isotropic material. In contrast, the mechanical properties of the pulp and core showed significant differences in both directions, demonstrating anisotropic characteristics. Additionally, the axial compressive strength of the Cerasus humilis fruit was higher than its radial compressive strength. The simulation results revealed that during axial compression, when the surface stress of the peel reached 0.08 MPa, the fruit completely fractured. The location and morphology of the cracks in the simulation were consistent with those observed in the experimental results. Furthermore, under different compression directions, the force–displacement curves obtained from actual compression tests closely aligned with those from the finite element simulations. The finite element model established in this study effectively simulates and predicts the cracking and internal damage behavior of Cerasus humilis fruit under compressive loads. This research provides a theoretical foundation and technical guidance for reducing mechanical damage during the harvesting process of Cerasus humilis.